The Concentration of Selected Inflammatory Cytokines (IL-6, IL-8, CXCL5, IL-33) and Damage-Associated Molecular Patterns (HMGB-1, HSP-70) Released in an Early Response to Distal Forearm Fracture and the Performed Closed Reduction With Kirschner Wire Fixation in Children - Tylicka, Marzena; Guszczyn, Tomasz; Maksimowicz, Michał; Kamińska, Joanna; Matuszczak, Ewa; Karpińska, Maria; Koper-Lenkiewicz, Olga Martyna (Frontiers in Endocrinology, 2021)
The evaluation of trauma after surgery through objective analysis of biochemical markers can help in selecting the most appropriate therapy. Thus the aim of the study was the evaluation of the concentration of selected inflammatory cytokines (IL-6, IL-8, CXCL5, IL-33), C-reactive protein (CRP), and damaged-associated molecular patterns (DAMPs): HMGB-1, HSP-70 in the plasma of children in response to bone fracture and investigation into how the closed reduction with percutaneous Kirschner wire fixation (CRKF) affected the levels of these molecules 12-14 hours after the surgical procedure. The conducted study would answer the question if the CRFK procedure leads to excessive production of inflammatory and damage markers. Blood samples from 29 children with distal forearm fractures were collected 30 min. before CRKF procedure and 12-14 hours after performance of the procedure. The control group was composed of 17 healthy children. IL-6 and CRP concentrations were analyzed using routinely performed in vitro diagnostics tests; the remaining proteins were analyzed with the use of the ELISA method. Increased values of IL-6, CRP, and HSP-70 represented an early inflammatory response to distal forearm fractures classified as SH-II type according to the Salter-Harris classification system. However, the median CRP concentration was within the reference values not indicative of the inflammatory state. The CRKF procedure may be a good solution for the treatment of bone fractures, as damaged associated molecular patterns – HMGB-1 and HSP-70 – did not significantly differ 12-14 hours after the approach was applied as compared to the control group. Moreover, the growth of IL-6 concentration after the CRKF procedure was 1.5-fold to the level before CRKF, while the increase of this marker in response to the distal forearm fracture was 4.3-fold compared with the control group. Based on this data, it appears reasonable to suggest that the CRKF approach caused less damage and inflammatory response in comparison to the response to the fracture.